Development of a Novel Spawn (Block Spawn) of an Edible Mushroom, Pleurotus ostreatus, in Liquid Culture and its Cultivation Evaluation. Issue 1 (2nd January 2019) - Zhang, Wei-Rui; Liu, Sheng-Rong; Kuang, Yun-Bo; Zheng, Shi-Zhong
Abstract: Mushroom cultivation has gained increased attention in recent years. Currently, only four types of spawn, including sawdust spawn, grain spawn, liquid spawn, and stick spawn, are commonly available for mushroom cultivation. This limited spawn diversity has led to difficulty in selecting suitable inoculum materials in some cultivation. In this study, three small blocks of lignocellulosic agro-wastes and one block of a synthetic matrix were prepared as support for growing Pleurotus ostreatus in liquid medium. Mycelium-adsorbed blocks were then evaluated for their potential as block spawn for fructification. Our results indicated that the edible fungus was adsorbed and abundantly grew internally and externally on loofah sponge and synthetic polyurethane foam (PUF) supports and also has the ability to attach and grow on the surface of sugarcane bagasse and corncob supports. The mycelia of P . ostreatus adhered on corncob exhibited the highest metabolic activity, while those on the PUF showed the least activity. Mycelial extension rates of block spawns made of agro-waste materials were comparable to that of sawdust spawn, but the block spawn of PUF showed a significantly lower rate. No significant differences in cropping time and yield were observed among cultivations between experimental block spawns and sawdust spawns. Moreover, the corncob block spawn maintained its fruiting potential during an examined period of 6-month storage. The developed block spawn could be practically applied in mushroom cultivation.